A study on the influence of communication state of wireless coupling system on heavy haul train and its operation - LIU Huawei; LIU Boyang; ZHU Jichao; AN Erjing; WEI Wei (机车电传动)
The communication delay or interruption of the wireless coupling control system would seriously affect the braking and release performance of a train, undermining its operation safety. For the purpose of this paper, the 10,000 t heavy haul formation of 2<alternatives>× <?fx-imagestate width="1.43933344" height="2.28600001"?> <?fx-imagestate width="1.43933344" height="2.28600001"?> </alternatives> SHEN 12 locomotives + 132<alternatives>× <?fx-imagestate width="1.43933344" height="2.28600001"?> <?fx-imagestate width="1.43933344" height="2.28600001"?> </alternatives>C64 cars for Shenmu-Shuozhou Railway was taken as an example, and the simulation method based on air flow theory and multi-rigid-body dynamics was employed to systematically analyze the braking and release characteristics, braking performance and coupler force of the train under communication delay or interruption, and the operation method under communication interruption was studied. The results show that as the communication delay increases, the exhaust and recharging times of train pipes, the coupler force and the braking distance increase, and the braking and release synchronization of the train decreases. Considering the level of improvement to the synchronization of train braking and release by the slave locomotive, the communication delay should be less than 6 s for the operation safety of train during cyclic braking. When a communication interruption occurs, the exhaust and recharging times of the train pipes increase, the braking wave and the release wave are only propagated backward from the master locomotive, and the synchronization of braking and release decreases. In addition, the slave locomotive does not apply electric braking force, resulting in a significant increase (up to 93.9%) in the tensile coupler force of the train under communication interruption when it is released. The train under communication interruption tends to adopt a two-step braking approach, namely reducing 50 kPa pressure as the first step, and then reducing the pressure to the target value as the second step, in which the maximum compression coupler force is significantly lower than that when the pressure is reduced to the target value by just one step. When the target pressure reduction is 60-100 kPa, the advantage of the two-step approach is more obvious than that of the one-step approach, and the maximum compression coupler force is less than 900 kN.